Eficiência de placas de argamassa de cimento com adição de limalha de ferro fundido na atenuação de raios X - Kasprisin, Luiz Fernando (2021)
Shielding is a basic factor for radiological protection, and it must be constructed of materials that provide the necessary attenuation to radiation. The sizing and choice of material depend on the type of radiation. Materials such as lead, barium mortar and concrete are commonly used as radiation protection barriers. Several factors influence the efficiency, including the required thickness. This research aims to analyze the efficiency of cement mortar slabs with the addition of cast iron filings in the attenuation of Xrays and thus aims to analyze the effectiveness of a material with the addition of a residue from industrial production. The research was carried out between 2019 and 2021, at the Materials Laboratories (DACOC) of UTFPR, campus Curitiba and Instituto LACTEC, Paraná. The cast iron filings were collected from a company where the industrial process is standardized, providing a residue that, when studied, the results can be extrapolated. The research focuses on radiological barriers prepared with cement mortar and additions. The analysis of the efficiency of cement mortar slabs with the addition of cast iron filings in the attenuation of Xrays showed that iron filings, replacing sand in cementitious slabs, have an attenuation coefficient close to that of concrete, for lower energies, between 70 and 90 keV. At energies above 125 keV, iron filings showed superior results to other materials (concrete and barium mortar). Therefore, the iron filings proved to be efficient, especially when subjected to tests at higher energies.